Association between occurrence of ossicular chain defect and osteoprotegerin gene expression in patients with chronic otitis media - ATA, PINAR (SPRINGER, 2019)
Objective Chronic otitis media (COM) is an important debilitating public problem causing hearing loss due to irreversible resorption of the ossicular chain. Activation of osteoprotegerin (OPG) during an acute attack of COM prevents bone resorption. The aim of the study was to investigate the role of OPG gene expression level on ossicular chain resorption in chronic otitis media. Materials and methods Fifty operated COM patients were included in the study. While 20 patients underwent ossiculoplasty, 30 patients underwent type 1 tympanoplasty. For RNA isolation and OPG gene expression analysis, middle ear swabs were taken from nasopharynx in the ostium of the Eustachian tube. RNA was isolated with mRNA easy kit and kept at - 85 degrees C till the cDNA and expression analysis. Expression levels were analyzed with real-time quantitative PCR in comparison with PDGB gene expression level as an internal control. Results Sample Cq measurements of type 1 tympanoplasty group were higher than Cq measurements of the internal control group (p = 0.027; p < 0.05). In contrast, there was no statistically significant difference between sample Cq measurements of ossiculoplasty group and Cq measurements of the internal control group (p = 0.293; p > 0.05). Conclusion Since OPG gene expression level was significantly higher in type 1 tympanoplasty group, OPG gene regulation system may have an effect on ossicular chain destruction in COM.
Keywords: Tympanoplasty; Ossiculoplasty; Osteoprotegerin; Gene expression